2004
DOI: 10.1016/j.physa.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Matrix product states of three families of one-dimensional interacting particle systems

Abstract: The steady states of three families of one-dimensional nonequilibrium models with open boundaries, first proposed in [22], are studied using a matrix product formalism. It is shown that their associated quadratic algebras have two-dimensional representations, provided that the transition rates lie on specific manifolds of parameters . Exact expressions for the correlation functions of each model have also been obtained. We have also studied the steady state properties of one of these models, first introduced i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 30 publications
(61 reference statements)
2
41
0
Order By: Relevance
“…It turns out that the dynamics of the position of a shock front is similar to that of a biased random walker moving on a finite lattice with reflecting boundaries. This steady-state probability distribution vector has also been obtained using a matrix product method in [14]. By associating the operators E and D to the presence of a vacancy and a particle in a given lattice site, the steady-state weight of any configuration…”
Section: Steady-statementioning
confidence: 99%
See 4 more Smart Citations
“…It turns out that the dynamics of the position of a shock front is similar to that of a biased random walker moving on a finite lattice with reflecting boundaries. This steady-state probability distribution vector has also been obtained using a matrix product method in [14]. By associating the operators E and D to the presence of a vacancy and a particle in a given lattice site, the steady-state weight of any configuration…”
Section: Steady-statementioning
confidence: 99%
“…In (4), |V and W | are two auxiliary vectors. It has been shown that these two operators and vectors have a two-dimensional matrix representation given by [14] …”
Section: Steady-statementioning
confidence: 99%
See 3 more Smart Citations